THE ROLE OF A FIRM’S NEGATIVE MEDIA COVERAGE OF CORPORATE SOCIAL RESPONSIBILITY PRACTICES IN PREDICTING THE SUPPLY OF CASH FLOW FORECASTS - Hua, Meiying; Groening, Christopher (International Journal of Accounting & Finance Review, 2022)
Analysts seek to provide investors with an accurate picture of firm value using tangible and intangible criteria. Researchers use one intangible measure, corporate social responsibility (CSR), to proxy for the firm’s relationship with its stakeholders. The purpose of this paper is to advance research in two ways. First, we examine cash flow forecasts because they are less subjective than earnings forecasts. Second, we focus on a firm’s corporate social irresponsibility (CSIR) reputation formed through negative media coverage of environmental, social, and governance practices. Our paper posits that analysts are less likely to provide cash flow forecasts for a firm with a poor CSIR reputation. We conducted a study with 50,365 firm-year observations over twelve years. We support our hypothesis after controlling for endogeneity: The likelihood of analyst cash flow forecast issuance is associated negatively with firm negative media coverage. Additional analyses show that numerous firm and industry-related variables moderate this effect. This decrease in cash flow forecast issuance likelihood occurs, even if the poor CSIR reputation is from as long ago as three years prior or is due to environmental, social, or governance issues. Furthermore, increases in cash flow volatility and capital intensity positively moderate the likelihood of issuing a cash flow forecast, while increases in ROA and Tobin’s q negatively moderate the likelihood of issuing a cash flow. JEL Classification Codes: M14, M40, M41.